Can community care workers deliver a falls prevention exercise program? A feasibility study - Burton, Elissa; Lewin, G.; O Connell, H.; Petrich, M.; Boyle, E.; Hill, Keith (Dove Medical Press Ltd., 2018)
Background: Almost half of older people receiving community care fall each year and this rate has not improved in the last decade. Falls prevention programs targeted at this group are uncommon, and expensively delivered by university trained allied health professionals. Purpose: To investigate the feasibility of community care workers delivering a falls prevention exercise program to older clients, at low or medium risk of falling, as part of an existing service provision. Patients and methods: Community care workers from 10 community care organizations participated in the training for, and delivery to their clients of, an 8-week evidence-based falls prevention exercise program. Community care workers included assessment staff (responsible for identifying the need for community care services through completing an assessment) and support workers (responsible for providing support in the home). Clients were surveyed anonymously at the completion of the intervention and workers participated in a semi-structured interview. Results: Twenty-five community care workers participated in the study. The falls prevention program was delivered to 29 clients, with an average age of 82.7 (SD: 8.72) years and consisting of 65.5% female. The intervention was delivered safely with no adverse events recorded, and the eligibility and assessment tools were completed by the majority of community care workers (93.1%). Assessment staff found it difficult to find time to deliver the intervention. Support workers were able to complete the intervention within their current service delivery period, with the initial assessment taking a small amount of additional time. Support workers reported enjoying the additional responsibility afforded by delivering the falls prevention program and seeing changes in their clients. The majority of clients (82%) reported enjoying the exercises, with 59% reporting that they felt it made a positive change in their health. Cl ients completed the exercises on average 4.8 (SD: 2.2) days per week. Conclusion: Community care workers who have completed appropriate training are able to deliver a falls prevention exercise program to their clients as part of their current services. Further research is required to determine whether the program reduces the rate of falls for community care clients and whether integration of a falls prevention program into an existing service is cost-effective.